(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Low light conditions pose significant challenges for image capture and processing, leading to degraded image quality with reduced visibility and increased noise. Traditional low light image enhancement methods typically involve hand-crafted image processing techniques, such as histogram equalization, contrast stretching, and noise reduction filters.